ANALISIS STRATEGI PENINGKATAN KINERJA KARYAWAN PADA PERUM DAMRI CABANG KABUPATEN MANOKWARI - anto, Nurwidi; Tata, jan Felarius (Cakrawala Management Business Journal, 2024)
ABSTRACT The purpose of this study was to find out the causes of the decline in employee performance at Perum Damri Manokwari Regency, and to find out the strategies used by the company to improve employee performance at Perum Damri Manokwari Regency Branch. This type of research uses qualitative methods with a descriptive approach. The sampling technique used purposive sampling and the data sources in this study were the three managers from each division who could represent their divisions, namely business managers, technical managers, HR finance managers and general public. The results showed that of the seven indicators (motivation, work discipline, career path, compensation, organizational climate, leadership, education and training) to see the causes of decreased employee performance at Perum Damri of Manokwari Regency, the factors that can cause decreased employee performance are in the climate aspect. organization, where even though the climate or work situation within the company is good among fellow employees, it's just that problems from outside the company or external factors are problems that can have a personal impact on the employees themselves which can lead to decreased employee performance